Artificial Intelligence's Impact on the Development of Islamic Religious Education Learning at a Public Junior High School of Cilegon, Indonesia - Wasehudin, Wasehudin; Aslihah, Aslihah; Sirojudin, Rumbang; Yuttana, Yuttana (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This study was conducted with the aim of knowing the existence of Artificial Intelligence (AI) in improving the quality of learning in Islamic Religious Education subjects. This study used a qualitative approach by using field observations and interviews to collect data. The research shows that educational institutions have felt the impact of technological advances and AI and have used these tools to improve the teaching and learning process. Education professionals recognize that these advancements are very beneficial in making the learning process more efficient and effective. Personalized learning, automated assessments, virtual tutoring, smart content, and presentation translation are some examples of the benefits of AI for education.